Assessment of Soil Moisture Variability for Urban Flood Risk Mitigation - Abhishek, Kumar Ayush; Ojha, Shashi Shankar (NG Civil Engineering, 2025)
Urban flooding has become a recurring problem in rapidly developing cities like Patna, primarily due to poor drainage, increased impervious surfaces, and a lack of integrated soil-based flood risk assessment. This study investigates the variability in soil moisture and its influence on urban flood susceptibility across selected locations in Patna. Soil samples were collected from ten urban sites and analyzed in the laboratory for texture (sand, silt, clay), water content, specific gravity, and field capacity. The results indicate a predominance of silt and clay-rich soils in many areas, particularly in Gulzarbagh, Gaighat, BIT, and Patrakar Nagar, contributing to low infiltration rates and increased surface runoff. Field capacity ranged from 9% to 21.41%, suggesting limited water retention capacity in several locations. The Soil Water Retention Curve (SWRC) was plotted using Brooks & Corey (1964), Campbell (1974), and Van Genuchten (1980) models with the help of SWRC v3.0 software to derive unsaturated hydraulic properties. Findings highlight that areas with finer-textured soils exhibit higher flood vulnerability due to reduced permeability and delayed infiltration. This soil-based assessment provides a scientific basis for integrating subsurface hydrological characteristics into urban flood mitigation and planning strategies for Patna and similar flood-prone urban centers.